Analysis of perioperative fertility-related stress and associated factors in women of childbearing age undergoing salpingectomy for ectopic pregnancy: a study based on the health ecology model - Li, Li; Guo, Zhen; Guo, Ya-Li; Li, Jing-Ping (Frontiers in Psychiatry, 2025)
ObjectiveThe objective of this study is to evaluate perioperative fertility-related stress and identify its correlative factors among women of childbearing age undergoing salpingectomy for ectopic pregnancy (EP).MethodsThis retrospective cross-sectional study involved women of childbearing age who underwent unilateral salpingectomy (on the affected side) for EP in the Department of Obstetrics and Gynecology at a tertiary hospital in Taiyuan, Shanxi Province, China, between March 2023 and September 2024. Sociodemographic information and clinical data were collected from all participants. Additionally, participants completed two validated questionnaires: the Fertility Problem Inventory (FPI), which assesses fertility-related stress, and the Perceived Social Support Scale. Statistical analysis was performed using SPSS 23.0 software to identify factors associating fertility-related stress.ResultsA total of 139 eligible women were included in the study. The mean fertility-related stress score of the patients was (148.39 ± 24.44), indicating high fertility-related stress. Factors associated with fertility-related stress covered all aspects of the health ecology model, including clinical and demographic characteristics (age, presence of lesions in the contralateral fallopian tube, and history of assisted reproductive technology use), psychological and behavioral characteristics (fertility intentions), interpersonal networks (perceived social support and number of children), working and living conditions (family monthly income per capita), and policy environment (degree of influence of traditional family fertility views).ConclusionWomen of childbearing age undergoing salpingectomy for EP experience high perioperative fertility-related stress. Our findings indicate that this stress is associated with factors across multiple levels, including clinical (e.g., older age, contralateral tubal lesions, history of ART), psychosocial (e.g., strong fertility intention, lower social support, having fewer children), and socioeconomic factors (e.g., lower income). These findings can guide healthcare providers in developing targeted interventions. Specifically, providers should not only focus on treatment outcomes but also address future fertility needs by assessing these key factors and leveraging social support networks to mitigate stress.